Formation of an RNA polymerase II pre-initiation complex on an RNA promoter derived from hepatitis delta virus in vitro - Abrahem F., Abrahem (University of Ottawa (Canada), 2010)
Hepatitis delta virus (HDV) is the smallest known RNA pathogen able to infect humans. It is a subviral agent that depends on hepatitis B virus (HBV) infection. As HDV does not possess its own polymerase, the virus is believed to depend upon the host DNA-dependent RNA polymerases (RNAPs) for its transcription and replication. Although RNAPs are able to use RNA as a template, how they recognize RNA promoters is unknown. In this study, I used a 199-nts HDV RNA fragment, corresponding to the right terminal stem-loop extremity of the genomic polarity (R199G; nts 1540 to 60) as a model to investigate the recognition of an RNA promoter by RNAP II. Inhibition of the transcription reaction using an antibody specific to the C-terminal domain (CTD) of the largest subunit of RNAP II, and the direct binding of purified RNAP II to the RNA promoter confirmed the involvement of RNAP II in this process. RNA affinity chromatography established the formation of an RNAP II pre-initiation complex on R199G, and that the formed complex contains the core RNAP II subunit and the general transcription factors TFIIA, TFIIB, TFIID, TFIIE, TFIIF, TFIIH, and TFIIS. I also found that the addition of free nucleotide triphosphates (NTPs) to the RNAP II pre-initiation complex formed on R199G caused the formation of an active initiation complex. As a result of the RNAP II complex activation, a short HDV RNA transcript was transcribed from R199G, and its 5' extremity was found to be located near the expected transcription start site of HDV mRNA (i.e. 1630). I also established the direct binding of the TATA-binding protein (TBP) to the RNA promoter, and suggested that this protein might be required for RNAP II complex nucleation on the RNA promoter. My findings represents a milestone in the study of the unconventional use of an RNA promoter 2 by RNAP II, and provide a better understanding of the events leading to the formation of the RNAP II pre-initiation complex on an RNA promoter.
Keywords: Chemistry, Biochemistry.